Productivity of Bali Cattle Fed Ration Supplemented by Molasses Containing Several Types of Defaunation Agents - AANBS Dinata; Yusti Pujiawati; Fawzan S Aurum (Jurnal Ilmu Ternak dan Veteriner, 2019)
Defaunation agents and molasses combination indicate able to improve digestibility of feed. This study was conducted to assest productivity of Bali Cattle fed ration supplemented with molasses solution containing several types of defaunation agents (moladef). Twenty Bali Cattle with average body weight of 307.56±52.46 kg were used in this research for six months. This study was arranged in a completely randomized design with four treatments and five replications. The treatments were P1 : Napier grass+pollard 1. 5 kg/head/day, P2 : napier grass + pollard 1. 5 kg/head/day + Hibiscus tiliaceus moladef 10 cc/head/day, P3 : napier grass + pollard 1. 5 kg/head/day + Hibiscus rosasinensis moladef, P4 : napier grass + pollard 1. 5 kg/head/day + Aloe vera moladef 10 cc/head/day . The parameters observed were average daily gain (ADG), feed intake, feed conversion ratio (FCR) and feed digestibility. This study suggest that the best average daily gain (ADG) was found in treatment P2 is 543,13 g/head/day. Treatment P2 also showed highest dry matter digestibility and crude fiber digestibility was 81,36% and 73,85%.  It is concluded that Bali Cattle fed on napier grass + pollard 1. 5 kg/head/day + Hibiscus tiliaceus moladef 10 cc/head/day resulted in the highest ADG and CF digestibility.